Isolation of a Melanoblast Stimulator from Dimocarpus longan, Its Structural Modification, and Structure–Activity Relationships for Vitiligo - Jae-Won Song; Sunju Choi; Gayeong Kim; Hyang Bok Lee; P. Sankara Rao; Jeonghyun Shin; Eun Ki Kim; Dong-Gyu Cho (Molecules, 2022)
A novel melanoblast stimulator (1) was isolated from Dimocarpus longan. Its analogs were also synthesized to support a new furan-based melanoblast stimulator scaffold for treating vitiligo. Isolated 5-(hydroxymethyl)furfural (HMF, 1) is a well-known compound in the food industry. Surprisingly, the melanogenic activity of HMF (1) was discovered here for the first time. Both HMF and its synthetic analog (16) promote the differentiation and migration of melanoblasts in vitro. Typically, stimulator (1) upregulated MMP2 expression, which promoted the migration of melanoblasts in vitro.